From the inventory to the mausoleum: the restitution of Cipriano Catriel remains through a historical approach (Museo de la Patagonia PNNH - APN) - Piantoni, Giulietta; Marinetti, Camila (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
After the 1983’s democratic restoration and the 1994’s constitutional reform, the public status of indigenous claims in Argentine movilized various requests for the restitution of human remains and cultural objects. Although most of them took place in La Plata Museum, the case we present requires a special study. We propose a historical approach of Cacique Cipriano Catriel’s skeletal remains and belongings as objects of the Patagonia Museum depending on Nahuel Huapi National Park and the National Parks Administration. We situate the case in the history of Argentine restitutions and, through the conflict’s reconstruction, we focus on the process of acquisition, institutional insertion and returning the skull and the poncho. With this purpose, we analyzed the judicial files located in the Museum. Our conclusions assemble some contributions to the study of human remains in their political plots through a historical approach.